2019
DOI: 10.5194/essd-2019-227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New continuous total ozone, UV, VIS and PAR measurements at Marambio 64° S, Antarctica

Abstract: A GUV multifilter radiometer was set up at Marambio, 64 • S 56 • W, Antarctica, in 2017. The instrument measures continuously ultraviolet (UV) radiation, visible (VIS) radiation and photosynthetically active radiation (PAR). The measurements are designed for providing high quality long-term time series which can be used to assess the impact of global climate change in the Antarctic region. The quality assurance includes regular absolute calibrations and solar comparisons performed at the site and at Sodankylä,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In the Antarctic Peninsula region, both Adhikari et al (2012), Lachlan-Cope (2010) and Scott et al (2017) found 205 the cloud cover minima in winter and maxima in summer. However, due to the large cloud cover variability, mentioned also in Aun et al (2020), the results presented in this study might have been affected by the choice of study period.…”
Section: Solar Uv Spectra Climatology and Changesmentioning
confidence: 85%
“…In the Antarctic Peninsula region, both Adhikari et al (2012), Lachlan-Cope (2010) and Scott et al (2017) found 205 the cloud cover minima in winter and maxima in summer. However, due to the large cloud cover variability, mentioned also in Aun et al (2020), the results presented in this study might have been affected by the choice of study period.…”
Section: Solar Uv Spectra Climatology and Changesmentioning
confidence: 85%